Serine-Arginine Protein Kinase 1 Regulates Ebola Virus Transcription - Yuki Takamatsu (American Society for Microbiology, 2020)
ABSTRACT Ebola virus (EBOV) causes a severe and often fatal disease for which no approved vaccines or antivirals are currently available. EBOV VP30 has been described as a viral phosphoprotein, and nonphosphorylated VP30 is essential and sufficient to support secondary transcription in an EBOV-specific minigenome system; however, phosphorylatable serine residues near the N terminus of VP30 are required to support primary viral transcription as well as the reinitiation of VP30-mediated transcription at internal EBOV genes. While the dephosphorylation of VP30 by the cellular phosphatase PP2A was found to be mediated by nucleoprotein, the VP30-specific kinases and the role of phosphorylation remain unknown. Here, we report that serine-arginine protein kinase 1 (SRPK1) and SRPK2 phosphorylate serine 29 of VP30, which is located in an N-terminal R26xxS29 motif. Interaction with VP30 via the R26xxS29 motif recruits SRPK1 into EBOV-induced inclusion bodies, the sites of viral RNA synthesis, and an inhibitor of SRPK1/SRPK2 downregulates primary viral transcription. When the SRPK1 recognition motif of VP30 was mutated in a recombinant EBOV, virus replication was severely impaired. It is presumed that the interplay between SRPK1 and PP2A in the EBOV inclusions provides a comprehensive regulatory circuit to ensure the activity of VP30 in EBOV transcription. Thus, the identification of SRPK1 is an important mosaic stone that completes our picture of the players involved in Ebola virus transcription regulation. IMPORTANCE The largest Ebola virus (EBOV) epidemic in West Africa ever caused more than 28,000 cases and 11,000 deaths, and the current EBOV epidemic in the Democratic Republic of the Congo continues, with more than 3,000 cases to date. Therefore, it is essential to develop antivirals against EBOV. Recently, an inhibitor of the cellular phosphatase PP2A-mediated dephosphorylation of the EBOV transcription factor VP30 has been shown to suppress the spread of Ebola virus. Here, we identified the protein kinase SRPK1 as a VP30-specific kinase that phosphorylates serine 29, the same residue that is dephosphorylated by PP2A. SRPK1-mediated phosphorylation of serine 29 enabled primary viral transcription. Mutation of the SRPK1 recognition motif in VP30 resulted in significant growth inhibition of EBOV. Similarly, elevation of the phosphorylation status of serine 29 by overexpression of SRPK1 inhibited EBOV growth, highlighting the importance of reversible phosphorylation of VP30 as a potential therapeutic target.